2002
DOI: 10.1111/j.1467-842x.2002.tb00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods: Measuring physical activity in public open space — an electronic device versus direct observation

Abstract: Objective: To evaluate the practicality and validity of using infra-red beam counters (IRBCs) to measure walking path use and overall park use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Further, user volume assessed by the infrared beam ranged from 20% under-estimation to 16% over-estimation. 15 This wide range of inaccuracy may be attributed to the inconsistency of the infrared counter in measurement-double counts, false counts, and an inability to distinguish between individuals can lead to overestimation; while simultaneous passage of two or more people, time-delay activation, and monitor placement (both height and location, as well as multiple entry points) can lead to underestimation. 15,23,30 Based on these results, infrared beams appear to be unreliable and inappropriate for measuring physical activity in outdoor, open areas, and areas with multiple entry points, like parks.…”
Section: Infrared Sensorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, user volume assessed by the infrared beam ranged from 20% under-estimation to 16% over-estimation. 15 This wide range of inaccuracy may be attributed to the inconsistency of the infrared counter in measurement-double counts, false counts, and an inability to distinguish between individuals can lead to overestimation; while simultaneous passage of two or more people, time-delay activation, and monitor placement (both height and location, as well as multiple entry points) can lead to underestimation. 15,23,30 Based on these results, infrared beams appear to be unreliable and inappropriate for measuring physical activity in outdoor, open areas, and areas with multiple entry points, like parks.…”
Section: Infrared Sensorsmentioning
confidence: 99%
“…23,26,30 Three studies found that active infrared counters were particularly vulnerable to errors when used in outdoor settings. 15,23,30 One 4-month study reported that the counter "represented a systematic 15% undercount of trail users." 30 Another study comparing infrared beam counters and direct observation of walking path and overall park use found the infrared beam over-estimated the number of people using the walking path by 14-78% and underestimated park use by 0-69%.…”
Section: Infrared Sensorsmentioning
confidence: 99%
See 3 more Smart Citations